An Exploratory Study of the Relationship Between Human Service Engagement, Recidivism and Completion of a Batterer Intervention Program - Morrison, Penelope K. (Journal of family violence, 2022)
Research on intimate partner violence shows that individuals who employ abusive behaviors also often have other psychosocial health problems (e.g., substance use) that may limit their ability to engage in treatment for abuse. Limited information exists regarding the psychosocial health needs of individuals who perpetrate abuse and how those needs play a role in their ability to follow through and complete an intervention program. Administrative data from one batterer intervention program (BIP) (N = 330), the local Department of Human Services, and court records were used to explore the relationship of service involvement to post-BIP recidivism. We found that over half the sample had engagement with DHS prior to starting the BIP, and general welfare, health and medical assistance, and behavioral health services were the most accessed programs. Additionally, recidivism for any crime was significantly higher among those with prior DHS involvement. Individuals who perpetrate abuse and who have a history of contact with DHS may represent the most vulnerable population with regards to both risk for attrition from a BIP and future recidivism. Future studies should seek to understand best practices for referrals and coordinated care for individuals who perpetrate abuse and ensure access to a broad range of services to help assist in reducing violent behaviors.